2018
DOI: 10.3389/fpsyg.2018.00196
|View full text |Cite
|
Sign up to set email alerts
|

Helpful and Hindering Factors in Psychodrama Field Training: A Longitudinal Mixed Methods Study of Student Development

Abstract: Although the literature indicates that students in mental health professions start to form their professional identity and competence in graduate school, there are few studies on the in-training experience of creative arts therapies students. This mixed methods study examined how five first-year students in a psychodrama master’s degree program in Israel experienced their field training, with the aim of identifying the factors likely to promote or hinder the development of their professional identity and sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Specifically, they often start to question their suitability for the helping profession (Orkibi, 2014). The decreased CSE among psychodrama students is also consistent with concerns over suitability reported in another study where psychodrama students indicated increased self‐doubts about their suitability (Azoulay & Orkibi, 2018). It may also be associated with a lack of a strong background in drama skills for some students when entering psychodrama training, which may have challenged their understanding of how drama is used in therapy (Orkibi, 2018), and thus impacted their domain‐specific CSE.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Specifically, they often start to question their suitability for the helping profession (Orkibi, 2014). The decreased CSE among psychodrama students is also consistent with concerns over suitability reported in another study where psychodrama students indicated increased self‐doubts about their suitability (Azoulay & Orkibi, 2018). It may also be associated with a lack of a strong background in drama skills for some students when entering psychodrama training, which may have challenged their understanding of how drama is used in therapy (Orkibi, 2018), and thus impacted their domain‐specific CSE.…”
Section: Discussionsupporting
confidence: 86%
“…CATs students' professional development has specific features related to the creative and expressive components of art-making that rely heavily on experiential training (Orkibi, 2018(Orkibi, , 2020. Student in-training experiences have generally been studied across CATs (Orkibi, 2010(Orkibi, , 2012a(Orkibi, , 2012b(Orkibi, , 2014, psychodrama (Azoulay & Orkibi, 2018), art therapy (Feen-Calligan, 2005), music therapy (Luce, 2008), dance-movement therapy (Federman, 2011), and drama therapy (Butler, 2017). 1 By contrast, this study was designed to examine changes in unstudied creative and personal factors in CATs students during their first year of graduate training.…”
mentioning
confidence: 99%
“…It is probably due to this association that the study of psychodrama’s effectiveness, in a controlled and more rigid academic way, has been neglected.” Nevertheless, the discovery of the therapeutic potency of spontaneity ( Moreno, 2010 ) and its effect on developing human interactions has been central to the process of recognizing the importance of psychodrama. The relevance of our study is directly linked to the discussion of the effects of psychodrama in several different contexts of application, clinical and non-clinical ( Kipper, 1978 ; D’Amato and Dean, 1988 ; Kipper and Hundal, 2003 ; Orkibi et al, 2017a , b ; Azoulay and Orkibi, 2018 ; Testoni et al, 2018 ) and to the need for solid methodologies that gather mixed approaches and acknowledge the complexity of this type of intervention, not always easily amenable to empirical research ( Kim, 2003 ). All in all, as stated by Kipper and Ritchie (2003 , p. 23) in their meta-analysis about the effectiveness of psychodramatic techniques, “the findings appear to shed a positive light on the issue of the validity of psychodramatic interventions and to encourage research regarding the specific psychotherapeutic effects of its basic techniques.”…”
Section: Introductionmentioning
confidence: 99%
“…Field training provides students essential opportunities to acquire supervised practical experience in applying clinical skills and knowledge in various settings (Azoulay & Orkibi, 2018). In 2020 and 2021, because of COVID-19 restrictions, field training was suspended for several months or shifted to online psychotherapy and supervision (King, 2020).…”
mentioning
confidence: 99%